Layout and Scheduling Optimization Problem for a Reconfigurable Manufacturing System - GAO, Sini; DAABOUL, Joanna; LE DUIGOU, Julien (International Journal of Industrial Engineering and Management, 2021)
Increased product variety leads manufacturers to adapt more flexible manufacturing systems such as the reconfigurable manufacturing system. This paper establishes a linear mathematical model to minimize the tardiness penalty for job shop scheduling and layout optimization in a Reconfigurable Manufacturing System. A small example solved by CPLEX software is used as a first step to validate the mathematical model. An improved Genetic Algorithm approach is introduced to search the approximate optimal solutions of this model in an efficient way and is tested using numerical experiments. Article history: Received (January 14, 2021); Revised (June 30, 2021); Accepted (July 2, 2021); Published online (September 08, 2021)